Active placebo versus standard placebo control interventions in pharmacological randomised trials - Laursen, David RT (Cochrane Database Syst Rev, 2020)
This is a protocol for a Cochrane Review (methodology). The objectives are as follows: To estimate differences in effects between pharmacological active placebo interventions and standard placebo interventions in randomised trials.